O Diário da Assembléia Geral de 1823 e os discursos de cidadania - Martins, Eduardo [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
O Diário cumpre a função de registrar a fala dos deputados da primeira Assembléia Constituinte do Brasil do ano 1823. Nas sessões parlamentares, procuram construir os acontecimentos e, a partir destes, um lugar específico para uma parcela dos indivíduos do Brasil, tais como os negros e os índios. Dessa forma o Diário é analisado como uma arma discursiva que ora produz práticas de não-cidadania, ora produz alteridades. Às vezes traz expresso nas suas entrelinhas denúncias de que estes indivíduos silenciados tentam negar o lugar a eles dedicados. Quando isso acontece, dá-se uma ruptura na tentativa da fabricação do acontecimento.

The Daily one fulfills the function to register says it of the members of the house of representatives of the first Constitutional conventional of Brazil of year 1823. In the parliamentary sessions these look for to construct to the events and from these a specific place for a parcel of the individuals of Brazil, such as the blacks and the indians. Of this form the Daily one is analyzed as a discursiva weapon that however produces practical of not-citizenship, however produces “alteridades”. To the times it brings Express in its space between lineses you denounce of that these silenced individuals try to deny the place dedicated they. When this happens gives a rupture in the attempt of the manufacture of the event.
The Daily one of the General meeting of 1823 and the speeches of citizenship The Daily one of the General meeting of 1823 and the speeches of citizenship
Keywords: Citizenship. Constituent assembly of 1823 and analyze of the speech; cidadania; Assembléia Constituinte de 1823; análise do discurso